2004
DOI: 10.1097/01.sla.0000143270.99191.10
|View full text |Cite
|
Sign up to set email alerts
|

A Pentadecapeptide Fragment of Islet Neogenesis-Associated Protein Increases Beta-Cell Mass and Reverses Diabetes in C57BL/6J Mice

Abstract: Because there is a deficiency of beta-cell mass in both type-1 and type-2 diabetes, INGAP peptide stimulation of fully functional neoislet differentiation may provide a novel approach for diabetes therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 40 publications
6
129
2
Order By: Relevance
“…Islet size analysis showed that the increase in ␤-cell mass resulted predominantly from an increase in the numbers of smaller islets, suggesting that AT possibly potentiated the appearance of new islets by neogenesis. Studies by Brand et al (6) and Rosenberg et al (32) indicate that, in the STZ rat model, islet neogenesis is a significant contributor to ␤-cell mass expansion. The use of a higher dose of AT, 40 mg/kg, also resulted in increased ␤-cell mass at PD 44 following STZ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Islet size analysis showed that the increase in ␤-cell mass resulted predominantly from an increase in the numbers of smaller islets, suggesting that AT possibly potentiated the appearance of new islets by neogenesis. Studies by Brand et al (6) and Rosenberg et al (32) indicate that, in the STZ rat model, islet neogenesis is a significant contributor to ␤-cell mass expansion. The use of a higher dose of AT, 40 mg/kg, also resulted in increased ␤-cell mass at PD 44 following STZ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The organization of INGAP's 175 amino acids classifies it as a member of the group 2 superfamily of reg-related proteins (Okamoto 1999). In addition to the biological efficacy of INGAP, a pentadecapeptide derived from the INGAP holoprotein retains biological activity (Rosenberg et al 2004). INGAP or INGAP-peptide administered to rodents (Rosenberg et al , 2004 or dogs (G Pittenger & D TaylorFishwick, unpublished observations) stimulates new islet growth as evidenced by elevated b-cell mass identified in quantitative histological and molecular analyses of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling has identified the Reg3 gene family as potentially involved in the stimulatory effect of RKIP1 ablation on pancreatic growth at P28. Interestingly, the Reg3 genes have been previously associated to pancreatic regeneration and islet cell neogenesis [37][38][39][40][41]. Further supporting a role for Reg3 genes in pancreatic postnatal development, a recent study has described the upregulation of Reg3 genes in the mouse pancreas between P7 and P30 followed by their subsequent downregulation in adulthood [42].…”
Section: Discussionmentioning
confidence: 83%